The Bolinao refugee ; Women [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Features Vietnamese refugees landing in Bolinao, Pangasinan ; interview with two activitists, Karina and Betty about their music ; and the interview with different people about women.
The Bolinao refugees (15 min.) -- Women (30 min.)
VHS.
Keywords: David , Karina Constantino -- Interviews; Abraham, Betty Basnillo -- Interviews; Refugees Vietnamese; Patriotic songs -- Philippines; Women -- Social conditions. -- Philippines